Misconception Identification with Two-Tier Test and POE Strategy to Improve Mass Balance Conceptual Comprehension in Industrial Chemical Major of Vocational High School - Ragil Sugeng Dewantoro; Subandi Subandi; Fauziatul Fajaroh (Jurnal Pendidikan Sains, 2017)
Abstract: This study used descriptive research and pre-experimental design. The first one was used to identify student misconception in the mass balance topic at macroscopic, sub-microscopic and symbolic levels. The second design aims to correct the misconceptions discovered by using the POE strategy. After three weeks the delayed test was done to find out the concept improvement using POE strategy. This design was also used to determine the effectiveness of POE strategies to achieve the aims. The results showed misconception on mass balance material with an average of 32.97%. The average POE effectiveness of 76.02% with high effectiveness criteria and retention of understanding with POE strategy after 2 weeks on average was 91.27% with very good criteria.Key Words: misconception, mass balance, POE, industrial chemistry, two-tier testAbstrak: Penelitian deskriptif dan pra eksperimen bertujuan untuk mengidentifikasi miskonsepsi siswa dalam neraca massa pada tingkat makroskopik, sub-mikroskopik dan simbolik. Sedangkan rancangan pra eksperimental bertujuan untuk memperbaiki miskonsepsi yang ditemukan dengan menggunakan strategi POE. Rancangan pra-eksperimental juga digunakan untuk mengetahui keefektifan strategi POE dalam memperbaiki miskonsepsi siswa pada materi neraca massa. Setelah tiga minggu dilakukan delayed test untuk mengetahui perbaikan konsep dengan strategi POE. Rancangan pra-eksperimental (pre-experimental) yang digunakan adalah modifikasi model one group pretest-posttest design dengan satu macam perlakuan. Hasil penelitian menunjukkan terjadi miskonsepsi pada materi neraca massa dengan rata-rata 32.97%. Selain itu didapatkan efektifitas POE rata-rata 76.02% dengan kriteria efektivitas tinggi dan retensi hasil remidi dengan strategi POE setelah 2 minggu rata-rata adalah 91.27% dengan kriteria sangat baik.Kata kunci: miskonsepsi, neraca massa, POE, kimia industri, test two tier